Regeneration of Pesantren Educational Ideas: A Study of the Alumni Network of Daar el-Qolam Islamic Boarding School - Weny Widyawati Bastaman; Yon Machmudi; Didik Pradjoko (Newinera Publisher, 2026)
Pesantren as the oldest Islamic educational institution in Indonesia faces the challenge of modernity that demands reform without losing its traditional identity. K.H. Ahmad Rifa’i Arief pioneered an integrative pesantren education model through Daar el-Qolam Islamic Boarding School that combines tradition and modernity. The urgency of this research lies in the importance of understanding the mechanism of pesantren educational idea regeneration so that its sustainability is maintained amid changing times. This study aims to analyze the process of regenerating pesantren educational ideas through the role of Daar el-Qolam alumni in Lebak Regency. The research method used a qualitative approach with a case study design. Data were collected through in-depth interviews, document studies, and observations of nine alumni pesantren as well as the JAMDAL and KAL communities. The data analysis technique followed the Miles and Huberman interactive model. The results showed that idea regeneration takes place through three main mechanisms: (1) internalization of values and a cadre formation system at Daar el-Qolam as the epicenter of ideas; (2) replication and adaptation of the educational model by alumni in establishing new pesantren; and (3) the formation of mutually supportive pesantren networks and ecosystems. These findings demonstrate that alumni not only reproduce the educational model but also become agents of transformation who safeguard the dignity and identity of pesantren at the community level. The conclusion is that successful idea regeneration requires synergy among the parent pesantren, alumni, and the community in a sustainable tripartite symbiosis.